Cerdas Saja Tidak Cukup, suatu Kajian Kecerdasan Majemuk (Kecerdasan Qur’ani) Tentang Ulil Albab - Ismail (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
The Qur'an discusses more comprehensive intelligence (syamil). perfect (kamil), and integral (mutakamil). The Qur'an is the Word of God, while the others are only human thoughts which are dominated by scular instincts. just being smart isn't enough, it takes a higher level than just being smart to achieve recognition of the greatness of God and submission to the Creator. This level can be called "ulil albab". This article aims to: describe how the substance of the concept of plural intelligence according to western experts and the concept of multiple intelligences according to the Qur'an and hadith. From the discussion it was concluded that Multiple Intelligence is a theory of multiple intelligences presented by Prof. Howard Gardner whose substance directs us that the potential of our children, especially if associated with intelligence, to understand multiple intelligence is not to make our children become great. However, the concept, at least can help us to understand that our children save tremendous potential that leads to a distance away from the intelligent substance itself that is distancing from understanding, living and practicing Islamic teachings in accordance with the provisions of the Koran and Al-Sunnah. If we as Muslims who feel as ulil albab, then always bite with molars (holding firm) the legacy of the Prophet Muhammad, before referring to other references.